The Application Of Google Earth In The Arrangement Of Industry And Trade Agglomeration Areas In Pekalongan City - Agus Ilyas; Tri Agus Setiawan; Sattriedi Wahyu Binabar; Eny Jumiati (Journal of INISTA, 2022)
Pekalongan City has a variety of potential areas that include the field of industry, services and trade or called agglomeration. The potential that exists is not only in the field of batik but also has beach tourism areas, culture, shopping, electronic trade, hotels, markets and so on. Based on the data from the Agency for Regional Development of Pekalongan City (Bappeda) in 2020 that in 2019 the investment growth was Rp. 3.29 trillion, the economic growth in the industrial sector was 4.84%, and the economic growth in the trade and services sector was 5.72%. Meanwhile, the economic income in 2019 in the Large Trade and Retail sector contributed the largest GDP of 21.79% while the smallest sector of the Water Supply, Waste Treatment, Waste and Recycling sector was 0.10%. With an area of 45.25 km² which has 4 sub-districts and 27 urban villages classified as a small area has limitation in choosing the ideal location, it is possible to have the emergence of centralization or concentration of industry in a certain area or on the other hand, there are several different types of centers and industries in one area because the area is very potential compared to other regions, this is in accordance with the spatial and regional planning (RTRW). For this reason, it is necessary to have a Geographic Information System (GIS) that is able to display the web-based agglomeration of industry and trade to ensure the quality and smooth flow of information about the existing potential. For this reason, the research that will be carried out uses the Research and Development (R&D) method, while the system development model used is Waterfall. In the creation and development of applications carried out with free and open-source software (Google Earth, global Mapper and others). The results of the research conducted can help the government in the context of making regional development policies based on the Geographic Information System of the Agglomeration of Industry and Trade so that between industry players there is no unfair competition but rather support and complement each other so as to increase the original income of the region, and investment for the achievement of the welfare of society